Unsur Psikis Tokoh Utama dalam Novel Elegi Haekal karya Dhia’an Farah - Salsabila Yulfi; Muhammad Adek (Departemen Bahasa dan Sastra Indonesia dan Daerah, 2023)
The objectives of this study are: (1) to describe the psyche elements of the main character in the novel Elegi Haekal by Dhia'an Farah, (2) to describe the impact of one of the elements that dominate in the novel Elegi Haekal by Dhia'an Farah. This research uses literary research with descriptive method. The object used in this research is the novel Elegi Haekal by Dhia'an Farah. Based on the results of the research, id, ego, and superego elements were found in Hanna's character and Jovan's character when faced with conflict. The id element is more dominated by Hanna's character, proven by the attitudes displayed by Hanna's character, namely selfishness and impulsiveness. Meanwhile, the superego element dominates Jovan's character, as evidenced by the attitudes displayed by Jovan's character, namely the attitude that upholds ethics and morals and the attitude of giving in. This can be seen from the way these characters deal with problems and make decisions to solve these problems, as well as by understanding the character’s psychological condition.